rihi Mesh Placement Algorithm In Collocation Methods - Edy Hermansyah; Annisa F. Edriani (Jurnal Komputer, Informasi dan Teknologi, 2024)
Various adaptive mesh selection strategies for solving single higher order two-points boundary value problems (BVPs) by using collocation methods are intensively investigated for along time and they are now well established. In this work we concern with numerical investigations of adaptive mesh selection algorithms using the criterion function rihi for solving first order system of BVPs and developing some algorithms. The algorithms perform quite nicely and appear competitive with De Boor algorithm.